Comeback of cashless communities an ethnographic study of online barter as a strategic response to economic difficulties during the COVID-19 pandemic - Lumayag, Nihikki Pauline B.; Tandog, Thea Kersti C. (2022)
This research study examines how members of the (Official) Cotabato Online Barter Community (OCBC) utilize online barter activities to strategically cope with economic difficulties during the COVID-19 pandemic. For the purpose of the study, active members, inactive members who were able to participate in barter activities, and the group administrator and moderators were included as research participants. It is guided by the principles of ethnography and the data collection strategies included online interviews, online surveys, and online participant and non-participant observation. The findings of the study generated from the informants? responses reveal that members of the OCBC utilize online barter to acquire basic necessities due to lack of monetary means resulting from the repercussions of the ecological disasters and stringent health protocols and hard lockdowns imposed as pandemic containment strategies, to dispose of underutilized goods, and to help and be able to ask for help from other barter members. Secondly, members facilitate barter exchanges by scrutinizing their relationship with their barter partners and their partners? Facebook profiles. A significant number of informants explained that they are not selective with their barter partners due to excessive competition within the group and abiding by specific rules and norms in the exchange process. Findings also reveal that participants interpret online barter based on how they utilize such practice and based on the traditional definition provided by scholars. Lastly, as evidenced by their responses, informants explained that they experience the online barter community as an actual community where barter transactions either fail or succeed. As a contribution to the literature on online barter, this study has attempted to explore the dynamics and mechanisms of an online barter community, demonstrate the conditions that fueled the prominence of online barter as an emerging phenomenon, and contextualize its origin.
Thesis (BS Anthropology) -- University of the Philippines Mindanao, July 2022